PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus di Desa Bayeman, Desa Ketowan dan Desa Kedungdowo Kecamatan Arjasa Kabupaten Situbondo) - Jannah, Siti Kholifatul; Arief, Mohammad Yahya; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2023)
Humans are the most important resource in an organization, agency or company. It would be difficult for an organization to carry out the mission and goals to be achieved without the human aspect. The purpose of this study is to analyze and investigate the impacts of work motivation and work environment on performance of village apparatus with job satisfaction as an intervening variable (case studies in Bayeman Village, Ketowan Village, and Kedungdowo Village, Arjasa District, Situbondo Regency). This research is an explanatory research. The population in this study are village apparatus in Bayeman Village, Ketowan Village, and Kedungdowo Village in Arjasa District, Situbondo Regency. The sampling technique used saturated sampling. Data analysis and hypothesis testing in this study used Partial Least Square Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis testing using Smart PLS 3.0 show that work motivation has a significant effect on job satisfaction, work motivation has a positive but not significant effect on employee performance, work environment has a positive but not significant effect on job satisfaction, work environment has a positive but not significant effect on employee performance, and job satisfaction has a positive but not significant effect on employee performance. The results of indirect effect hypothesis testing show that work motivation has a positive but not significant effect on performance through job satisfaction, and work environment has a positive but not significant effect on performance through job satisfaction.